2014
DOI: 10.1016/j.ijhydene.2014.07.121
|View full text |Cite
|
Sign up to set email alerts
|

Geologic storage of hydrogen: Scaling up to meet city transportation demands

Abstract: 12Over the last decade, there has been a growing interest in large-scale use of hydrogen in the transportation and 13 renewable energy sectors. Relatively cost-effective storage options at scale are essential to realize the full potential 14 of hydrogen as an energy carrier. Underground geologic storage of hydrogen could offer substantial storage cost 15 reductions as well as buffer capacity to meet possible disruptions in supply or changing seasonal demands. Several 16 geologic storage site options are being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
119
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(158 citation statements)
references
References 17 publications
0
119
0
1
Order By: Relevance
“…In this present study, CO 2 from biogas digesters is considered as a potential CO 2 source for methanation. Figure 2 demonstrates the RNG-production where CO 2 is captured from biogas digestion [13,22,23]. .…”
Section: Power-to-gas To Renewable Natural Gas 'Methanation'mentioning
confidence: 99%
See 1 more Smart Citation
“…In this present study, CO 2 from biogas digesters is considered as a potential CO 2 source for methanation. Figure 2 demonstrates the RNG-production where CO 2 is captured from biogas digestion [13,22,23]. .…”
Section: Power-to-gas To Renewable Natural Gas 'Methanation'mentioning
confidence: 99%
“…Power-to-Gas-to-renewable natural gas (Methanation)[13,22,23].A recent series of publications have studied the implementation of different power-to-gas pathways in the Canadian province of Ontario.Mukherjee et al (2017) [24], Hajimiragha et al (2009) [25], and Walker et al (2015) [26] examined the utilization of hydrogen via power-to-gas in the transportation sector. Additionally, Walker et al (2016) [27] and Al-Subaie et al (2017)[17] studied the implementation of electrolytic hydrogen into the petroleum-industry, aiming to optimize GHG reduction and system cost.…”
mentioning
confidence: 99%
“…Several studies have demonstrated the availability of underground hydrogen storage in Northern Germany [66], Poland [67], and Romania [68], as well as the technical feasibility of hydrogen storage generally [69]. However, the availability of hydrogen storage options near large cities causes large cost disparities [70]. The costs of geologic hydrogen storage are based on CAES geologic storage and adjusted for their respective energy densities [54].…”
Section: Hydrogen Electrolysis and Storagementioning
confidence: 99%
“…A report from the International Energy Agency (IEA) compares these underground storages from different points of view including safety, economy (capital and operational cost), as well as technical feasibility [32]. The results indicate that salt caverns are the best option for underground storage [36,84], however, the storage cost of depleted oil and gas reservoirs seems to be lower based on a study by Lord et al [85]. The compression pressure levels can vary in the range of 20 to 180 bar for underground storage [86].…”
Section: Hydrogen Storage and Compressionmentioning
confidence: 99%
“…Lord et al [85] listed the levelized capital cost of hydrogen for underground storage for different methods including salt caverns and depleted oil and gas reserves to be in the range of $1.2-2.2 per kg hydrogen. However, the levelized capital cost of hydrogen storage is strongly dependent on the type of underground storage and the amount of storage.…”
Section: Economic Analysismentioning
confidence: 99%